Perbandingan Pertumbuhan Saccharomyces cerevisiae dengan Kandungan Hidrogen Peroksida Dalam Substrat Berbasis Gula Serat Diperkaya Sari Stroberi: Comparison of Saccharomyces cerevisiae Growth with Hydrogen Peroxide Content in Strawberry Juice Enriched Fiber Sugar Based Substrate - Tresna, Adira Tatus; Syauqi, Ahmad; Ramadhan, Majida (Jurnal SAINS ALAMI (Known Nature), 2025)
The growth of Saccharomyces cerevisiae involves several factors that affect the survival and reproduction of the microorganism, one of which is the carbon substrate that is key to its growth. Fibre sugar-based substrates are glucose-containing materials with residual peroxide. They are often used as a source of nutrients in various biotechnological processes, particularly in bioenergy production, and can be used to support the growth of Saccharomyces cerevisiae. Strawberries (Fragaria sp.) are red due to their rich anthocyanin colour pigment, high in antioxidants and vitamin C. Antioxidants are considered very effective in reducing the action of oxidizers such as hydrogen peroxide (H2O2). This study aims to determine the effect of strawberry juice concentration on the growth of Saccharomyces cerevisiae with peroxide content in the medium. The research method used the randomized block design method, with variations in the concentration of strawberry juice 0%, 5%, 10%, 15%, and 20%, with 7x replicates for 7 days within a period of every 24 hours. The results showed that the content of strawberry juice is needed to increase growth. The 10% concentration had the same growth increase as the 0% extract concentration, but the number of cells was lower at 10,719,205 compared to 21,108,805. There is an effect of strawberry juice antioxidant substances on the growth of Saccharomyces cerevisiae fungal cells at a peroxide concentration of 1000 ppm in the medium.  Keywords: Saccharomyces cerevisiae, Hydrogen peroxide, strawberry, turbidimeter Pertumbuhan Saccharomyces cerevisiae melibatkan beberapa faktor yang mempengaruhi kelangsungan hidup dan reproduksi mikroorganisme tersebut, salah satunya yaitu substrat karbon yang menjadi kunci untuk pertumbuhannya. Substrat berbasis gula serat adalah bahan yang mengandung glukosa dengan residu peroksida dan sering kali digunakan sebagai sumber nutrisi dalam berbagai proses bioteknologi, khususnya dalam produksi bioenergi. Substrat berbasis gula serat dapat digunakan untuk mendukung pertumbuhan Saccharomyces cerevisiae. Buah Stroberi (Fragaria sp.) yang berwarna merah disebabkan kaya akan pigmen warna antosianin, tinggi antioksidan, dan vitamin C. Antioksidan dianggap sangat efektif menurunkan kerja oksidator seperti hidrogen peroksida (H2O2). Penelitian ini bertujuan untuk mengetahui pengaruh kosentrasi sari stroberi terhadap pertumbuhan Saccharomyces cerevisiae dengan kandungan peroksida dalam medium. Metode penelitian menggunakan metode Rancangan Acak Kelompok, dengan variasi konsentrasi sari stroberi 0%, 5%, 10%, 15%, dan 20%, dengan 7x ulangan selama 7 hari dalam kurun waktu tiap 24 jam. Hasil penelitian didapatkan kandungan sari stroberi dibutuhkan untuk memperoleh peningkatan pertumbuhan. Konsentrasi 10% terjadi peningkatan pertumbuhan yang sama seperti konsentrasi ekstrak 0%, tetapi jumlah sel lebih rendah yaitu 10.719.205 dibanding 21.108.805. Adanya pengaruh zat antioksidan sari stroberi terhadap pertumbuhan sel jamur Saccharomyces cerevisiae pada konsentrasi peroksida 1000 ppm dalam medium.    Kata kunci: Saccharomyces cerevisiae, Hidrogen peroksida, stroberi, turbidimeter